HUBUNGAN ANTARA BAURAN PEMASARAN DENGAN LOYALITAS PASIEN RAWAT JALAN DI RUMAH SAKIT DAERAH KALISAT KABUPATEN JEMBER TAHUN 2017 - Yuliasfa Sirrul Hayati; Christyana Sandra; Yennike Tri Herawati (Fakultas Kesehatan Masyarakat, Universitas Jember, 2018)
Marketing mix in hospital is ​​a group of controllable variables that can be used by hospitals to influence the reaction of service buyers. The marketing mix consisting of 7P (Product, Price, Place, Promotion, Process, Person, and Physical Evidence) can affect patient loyalty. This study aims to analyze the relationship between marketing mix and patient loyalty. The study method used is analytic with cross sectional design. The sample of study is 90 respondents using systematic random sampling technique. The result showed that most respondents rated the product mix (82%), the price mix (81%), the place mix (72%), the process mix (79%), the mix (84%), and the physical evidence mix (82% ) is good. However, most respondents rated promotion mix (92%) classified as less good. Based on the results, it is concluded that there is no significant relation between place mix and physical proof mix with patient loyalty, and there is significant relation between product mix, price mix, promotion mix, and process mix with patient loyalty. To increase loyalty patients can improve or maintain product mix, price mix, promotion mix, process mix, and people mix.